Takayasu's Arteritis: A Case Report - Arzoo Khadka; Sumi Singh; Sarika Timilsina (Journal of Nepal Medical Association, 2022)
Takayasu's arteritis is a chronic vasculitis of medium and large vessels. The most involved vessel is the aorta and its major branches. The disease is primarily seen in young women. The described incidence of the disease ranges from 0.3 to 3.3 million per year. The vessels are characterized by mononuclear infiltration and granulomatous inflammation of vascular media, which leads to arterial wall thickening with stenosis, occlusion, and aneurysmal dilation. Here we present a case of Takayasu's arteritis in a 26-year-old woman who presented with syncope and dizziness with thickened walls of the arch of the aorta and its branches in Magnetic Resonance Imaging angiogram finding. Women of Japanese descent are not the only ones who can develop Takayasu's arteritis; it can affect anyone. Therefore, early diagnosis and treatment are warranted. When the disease is dormant, the outcome seems favourable.